Outcomes-Based Conditionality : Its Role and Optimal Design - Ivanova, Anna (IMF Working Papers; Working Paper ;, 2006)
The paper employs a principal-agent framework to analyze the role and design of outcomesbased conditionality in the presence of market frictions and domestic opposition. The results suggest that outcomes-based conditionality is a good option for the IMF when opposition to reforms is relatively weak and when the IMF loan is unsubsidized. The only role conditionality ends up playing in this case is that of an efficiency tool. The benefits of outcomes-based conditionality in the presence of strong opposition are less clear, and using this conditionality as an incentive tool would require that IMF financing be subsidized.